M PEMBELIAN SECARA ANGSURAN DENGAN SISTEM WAGEAN PERSPEKTIF HUKUM EKONOMI SYARI’AH DI DESA NGUMPUL JOGOROTO JOMBANG: PURCHASE IN INSTALLMENTS USING THE WAGEAN SYSTEM SYARI'AH ECONOMIC LAW PERSPECTIVE IN THE VILLAGE OF NGUMPUL JOGOROTO JOMBANG - Amilatus Sholihah; Masrokin; Pratanto Rahayu, Wedi (Irtifaq, 2024)
This article discusses the about of the practice of buying and selling in installments with the wage system in Ngumpul Village from the perspective of sharia economic law. The practice of buying and selling in installments is an alternative for the people of Ngumpul Village in meeting household needs. In the mechanism of buying and selling in installments with the wage system from the perspective of sharia economic law, there is a divine economy, a moral economy, a humanitarian economy, and a balance economy. However, there are only three principles of sharia economics that have been applied in the moral economy, the humanitarian economy, and the welfare economy. Meanwhile, the divine economy has not been applied in the practice of buying and selling in installments with the wage system in Ngumpul Village.